Innovation in Islamic Social Finance: Integration of Digital Waqf and Sharia Crowdfunding in Indonesia - Sudi, Didih Muhamad (West Science Islamic Studies, 2025)
This study explores the integration of digital waqf and sharia crowdfunding in Indonesia, focusing on its potential to enhance Islamic social finance and contribute to sustainable development. Through qualitative analysis of interviews with five key informants, the research identifies the opportunities and challenges of combining these two financial instruments. The findings highlight the potential to expand access to funding, increase transparency, and align with Islamic values of charity and social justice. However, challenges such as regulatory uncertainty, technological limitations, and trust concerns need to be addressed for successful implementation. The study concludes that the integration of digital waqf and sharia crowdfunding can significantly contribute to social welfare and sustainable development in Indonesia, provided that regulatory frameworks are strengthened, technological infrastructure is improved, and public awareness is raised.